In vivo evaluation of axial integrity of coronary stents using intravascular ultrasound: Insights on longitudinal stent deformation. Issue 3 (14th December 2013) - Dvir, Danny; Kitabata, Hironori; Barbash, Israel M.; Minha, Sa'ar; Badr, Salem; Loh, Joshua P.; Chen, Fang; Torguson, Rebecca; Waksman, Ron
<x xml:space="preserve">Abstract</x> Objective To evaluate the axial integrity of different coronary stents using intravascular ultrasound (IVUS). Background Longitudinal stent deformation was recently reported. Methods Consecutive patients who underwent IVUS analysis after drug‐eluting stent (DES) implantation for de novo coronary lesions were evaluated. Stent length was compared with label length for calculation of absolute change and relative difference (absolute change divided by label length). Results A total of 233 DES utilizing five different platforms were included. The median absolute change in stent length was 0.90 mm (interquartile range [IQR] 0.48–1.39) and the relative difference was 5.24% (IQR 2.55–8.29). There was no significant difference among the groups in median absolute or relative change: Cypher 0.89 mm/3.89%, Taxus 0.88 mm/5.39%, Endeavor 1.16 mm/6.77%, Xience V 0.86 mm/5.80%, and PROMUS Element 0.79 mm/5.34% (P = 0.085, P = 0.072, respectively). Multivariate logistic regression revealed that the Cypher stent was independently correlated with a lower change in length, whereas stent label length and deployment pressure were correlated with higher absolute change. Conclusion The axial integrity of DES platforms examined in vivo was high, with only mild changes in stent length after implantation. While there are differences between first‐ and second‐generation DES, axial integrity among second‐generation DES was similar. © 2013 Wiley Periodicals, Inc.